2019
DOI: 10.1016/j.renene.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A resistive-capacitive model of pile heat exchangers with an application to thermal response tests interpretation

Abstract: • A new finite cylindrical source model with adiabatic surface is developed. • A new resistive-capacitive semi-analytical pile heat exchanger model is developed. • The new model improves the assessment of pile thermal performance. • Neglecting heat capacitance in the pile leads to an underestimation of performance. • The new model is successfully used to interpret a thermal r esponse test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The investigation was also undertaken with t min * = 3. Regarding set C, previous studies [12] reported λ m between 1.35 and 1.45 W•K•m −1 depending on the values chosen for t min * (from 5 to 7) and t max (from 250 h to 350 h) so this new analysis is consistent with previous work.…”
Section: Analysis Approachsupporting
confidence: 89%
See 4 more Smart Citations
“…The investigation was also undertaken with t min * = 3. Regarding set C, previous studies [12] reported λ m between 1.35 and 1.45 W•K•m −1 depending on the values chosen for t min * (from 5 to 7) and t max (from 250 h to 350 h) so this new analysis is consistent with previous work.…”
Section: Analysis Approachsupporting
confidence: 89%
“…Initially developed for BHE, the model described in Equations ( 1) and ( 3) do not account for the thermal inertia of the backfilling material. Past work shows that this purely resistive model (Figure 2a) is not suitable for pile heat exchangers of large diameters [11,12], since once λ m and R b have been fitted, the temperature change at small time scales (e.g., 1-10 h) is overestimated by several • C, leading to an underestimation of the transfer capacity of the PHE. Moreover, the duration required to thermally load the backfill material t min * is barely compatible with the operational constraints of a construction site.…”
Section: The Thermal Conductivity Of the Ground λmentioning
confidence: 99%
See 3 more Smart Citations